Iridium-doped ZIFs-derived porous carbon-coated IrCo alloy as competent bifunctional catalyst for overall water splitting in acid medium. (1st June 2019) - Sun, Xuechu; Liu, Fei; Chen, Xiu; Li, Cuicui; Yu, Jun; Pan, Mu
Abstract: Bifunctional electrocatalysts for overall water splitting in acidic media is critical for polymer electrolyte membrane (PEM) electrolysis of water. We report a synthesis of porous carbon-coated noble metal-based catalysts. We adopt simple annealing strategy involving Ir-doped zeolite imidazole skeleton to obtain IrCo alloys encapsulated by the porous carbon layers and carbon nanotubes, which is a new method for synthesizing IrCo alloy. The amount of Ir loaded in IrCo NPs catalyst is extremely low (only 6.7 wt%) and IrCo NPs exhibit excellent catalytic activity for both HER and OER in acidic environment, to achieve 10 mA cm −2 current density during HER and OER, overpotential of only 23.9 and 270 mV is required for our novel IrCo NPs catalyst. More significantly, IrCo NPs reach 10 mA cm −2 during overall water splitting at a cell voltage of only 1.55 V in 0.5 M H2 SO4 and demonstrated good durability. Thus, it has excellent prospects to be implemented into PEM for water electrolysis.